ISOLASI DAN IDENTIFIKASI Azotobacter DARI RHIZOSFER TANAMAN KOPI (Coffea canephora) YANG TERSERANG NEMATODA PARASIT Pratylenchus coffeae - Aditya Tanjung Yulitaasary; Iis Nur Asyiah; Mochammad Iqbal (saintifika, 2017)
Azotobacter is one group of aerobic bacteria that colonizes root surfaces and is able to produce glyceroline promoting substances, cytokines and Indole Acetate Acid (IAA). Azotobacter can be found in the rhizosphere of various types of plants, such as soy rhizosphere (Glycinemax L.), rhizosphere palm (Elaeis guineensis), coffee (Coffea arabica), and corn (Zea mays). Rhizosphere is a soil zone that surrounds the roots of plants where biology and soil chemistry are affected by roots. This zone has a width of about 1 mm. In this study rhizosphere used is rhizosphere coffea Robusta plant. The purpose of this research is to know the isolated Azotobacter isolate from the rhiszosphere of Robusta coffee plant which attacked by Pratylenchus coffeae parasite parasite from Kalibendo plantation, Banyuwangi. The type of research used is explorative research. In this research successfully obtained 5 bacterial isolates. The result showed that from isolate isolate, 4 isolates were genus Azotobacter while 1 isolate was not known.